Association between gene expression signatures and clinical outcomes of pembrolizumab versus paclitaxel in advanced gastric cancer: exploratory analysis from the randomized, controlled, phase III KEYNOTE-061 trial - Shitara, Kohei; Di Bartolomeo, Maria; Mandala, Mario; Ryu, Min-Hee; Caglevic, Christian; Olesinski, Tomasz; Chung, Hyun Cheol; Muro, Kei; Goekkurt, Eray; McDermott, Raymond S; Mansoor, Wasat; Wainberg, Zev A; et al. (Journal for ImmunoTherapy of Cancer, 2023)
BackgroundIn the randomized, controlled, phase III KEYNOTE-061 trial, second-line pembrolizumab did not significantly prolong overall survival (OS) versus paclitaxel in patients with PD-L1-positive (combined positive score ≥1) advanced gastric/gastroesophageal junction (G/GEJ) cancer but did elicit a longer duration of response and offered a favorable safety profile. This prespecified exploratory analysis was conducted to evaluate associations between tumor gene expression signatures and clinical outcomes in the phase III KEYNOTE-061 trial.MethodsUsing RNA sequencing data obtained from formalin-fixed, paraffin-embedded baseline tumor tissue samples, we evaluated the 18-gene T-cell-inflamed gene expression profile (TcellinfGEP) and 10 non-TcellinfGEP signatures (angiogenesis, glycolysis, granulocytic myeloid-derived suppressor cell (gMDSC), hypoxia, monocytic MDSC (mMDSC), MYC, proliferation, RAS, stroma/epithelial-to-mesenchymal transition/transforming growth factor-β, WNT). The association between each signature on a continuous scale and outcomes was analyzed using logistic (objective response rate (ORR)) and Cox proportional hazards regression (progression-free survival (PFS) and OS). One-sided (pembrolizumab) and two-sided (paclitaxel) p values were calculated for TcellinfGEP (prespecified α=0.05) and the 10 non-TcellinfGEP signatures (multiplicity-adjusted; prespecified α=0.10).ResultsRNA sequencing data were available for 137 patients in each treatment group. TcellinfGEP was positively associated with ORR (p=0.041) and PFS (p=0.026) for pembrolizumab but not paclitaxel (p>0.05). The TcellinfGEP-adjusted mMDSC signature was negatively associated with ORR (p=0.077), PFS (p=0.057), and OS (p=0.033) for pembrolizumab, while the TcellinfGEP-adjusted glycolysis (p=0.018), MYC (p=0.057), and proliferation (p=0.002) signatures were negatively associated with OS for paclitaxel.ConclusionsThis exploratory analysis of tumor TcellinfGEP showed associations with ORR and PFS for pembrolizumab but not for paclitaxel. TcellinfGEP-adjusted mMDSC signature was negatively associated with ORR, PFS, and OS for pembrolizumab but not paclitaxel. These data suggest myeloid-driven suppression may play a role in resistance to PD-1 inhibition in G/GEJ cancer and support a strategy of considering immunotherapy combinations which target this myeloid axis.Trial registration number NCT02370498.